Peningkatan Keterampilan Membaca Permulaan Menggunakan Kartu Siswa di Kelas II SD Negeri 36 Pontianak Kota - Santri Santri; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Departement of Mathematics Education, 2023)
This study aims to describe using card media to improve the beginning reading skills of grade II students at SD Negeri 36 Pontianak Kota. This research uses a descriptive method in the form of classroom action research (CAR) and is collaborative. The location of the research took place at Public Elementary School 36 Pontianak Kota, class II, with a total of 27 people who were used as subjects. The data collection technique used was observation and test techniques with data collection instruments namely observation sheets and test questions. This research was conducted in two cycles with one meeting each cycle. The results of the learning implementation design research (RPP) from cycle I average score of 3.32 and cycle II average score of 3.8. The results of the initial reading skills of the first cycle average score of 65.00 and the second cycle average score of 80.30. Based on the data obtained, it can be concluded that there is an increase in each cycle. Thus research using card media in class II can improve beginning reading skills.